2010
DOI: 10.1002/ppul.21308
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha in experimental empyema thoracis

Abstract: We describe a simple and effective rat model of empyema. TNF-α levels above 150 pg/ml in the pleural fluid are useful to confirm empyema, but cannot predict the severity of the inflammatory response. TNF-α levels below 150 pg/ml are useful to rule out empyema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several experimental models of empyema are available, with different animals, including rabbits, guinea pigs, and rats . Previous studies have shown that rat models are useful to evaluate diagnostic tests, and also that these models effectively reproduce infected pleural effusion .…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental models of empyema are available, with different animals, including rabbits, guinea pigs, and rats . Previous studies have shown that rat models are useful to evaluate diagnostic tests, and also that these models effectively reproduce infected pleural effusion .…”
Section: Discussionmentioning
confidence: 99%